Pseudocholinesterase Deficiency in an Indian Community - Ramaiah, Maddi; Ramakrishna, Prudhivi (Journal of Pharmacy Practice and Community Medicine)
Background: India, the seventh largest country, 3rd largest standing army and one of the oldest civilizations in the world, with a literacy rate of 74.04%. Indian population was a mixture of 46,73,034 categories of different castes and sub-caste each related to a specific occupation. Arya Vysya is a Hindu Indian caste with a total population of 22,952,000. Methods: Pseudocholinesterase is a glycoprotein enzyme with complex molecular structure synthesized in the liver and specifically hydrolyzes certain exogenous cholinesters. Pseudocholinesterase deficiency is a genetic enzyme abnormality or acquired alteration in the metabolism of choline esters in this patient may experience a paralysis of the respiratory muscles, to overcome this, required more time mechanically-assisted breathing. The presence of the genetic defect is not realized until one is exposed to succinylcholine or mivacurium. Results: Arya Vysya community people of India having deficiency of pseudocholinesterase is the most affected people than any other with homozygous mutation incidence rate of 2-4%. Very recent studies in 2016 reveal that malnutrition-induced pseudocholinesterase deficiency is also a possible etiology. Conclusion: It was suggested that the Arya Vysya Community people with a history of pseudocholinesterase deficiency should tell his or her doctor if when they undergo anesthesia for surgery to avoid potentially serious unwanted adverse effects.
Keywords: India; Arya Vysya; Pseudocholinestase; Pseudocholinestrase deficiency; Choline esters; Acholest test paper